Travelling wave solutions for the Richards equation incorporating non-equilibrium effects in the capillarity pressure. (June 2018) - van Duijn, C.J.; Mitra, K.; Pop, I.S.
Abstract: The Richards equation is a mathematical model for unsaturated flow through porous media. This paper considers an extension of the Richards equation, where non-equilibrium effects like hysteresis and dynamic capillarity are incorporated in the relationship that relates the water pressure and the saturation. The focus is on travelling wave solutions, for which the existence is investigated first for the model including hysteresis and subsequently for the model including dynamic capillarity effects. In particular, such solutions may have non monotonic profiles, which are ruled out when considering standard, equilibrium type models, but have been observed experimentally. The paper ends with numerical experiments confirming the theoretical results.